Beta‐glucans from oats and/or barley in a ready‐to‐eat cereal manufactured via pressure cooking and reduction of blood‐glucose rise after consumption: evaluation of a health claim pursuant to Article 13(5) of Regulation (EC) No 1924/2006. (8th April 2021) - ,; Turck, Dominique; Castenmiller, Jacqueline; De Henauw, Stefaan; Hirsch‐Ernst, Karen Ildico; Kearney, John; Knutsen, Helle Katrine; Maciuk, Alexandre; Mangelsdorf, Inge; McArdle, Harry J; Naska, Androniki; Pelaez, Carmen; et al.
Abstract: Following an application from Nestlé S.A. submitted for authorisation of a health claim pursuant to Article 13(5) of Regulation (EC) No 1924/2006 via the Competent Authority of Belgium, the EFSA Panel on Nutrition, Novel Foods and Food Allergens (NDA) was asked to deliver an opinion on the scientific substantiation of a health claim related to beta‐glucans from oats and/or barley in a ready‐to‐eat cereal manufactured via pressure cooking and reduction of blood glucose rise after consumption. The scope of the application was proposed to fall under a health claim based on newly developed scientific evidence. The food proposed is 'beta‐glucans from oats and/or barley incorporated into ready‐to‐eat breakfast cereals manufactured via pressure cooking'. The applicant proposed that at least 1.3 g of beta‐glucans/25 g of available carbohydrates in ready‐to‐eat breakfast cereals manufactured via pressure cooking should be consumed. Beta‐glucans from oats, barley or any combination thereof incorporated into ready‐to‐eat cereals manufactured by pressure cooking, are sufficiently characterised. The claimed effect proposed is 'reduction of the blood glucose rise after the meal'. The reduction of post‐prandial glycaemic responses (as long as post‐prandial insulinaemic responses are not disproportionally increased) may be a beneficial physiological effect. One human intervention study showed an effect of beta‐glucans from oats and/or barley, incorporated into breakfast cereals manufactured via pressure cooking at a level of at least 1.2 g/25 g available carbohydrates, on decreasing post‐prandial glycaemic responses without disproportionally increasing insulinaemic responses. Dose–response relationships were not tested, and no evidence has been provided that beta‐glucans incorporated into cereals processed using pressure cooking would exert a higher effect on post‐prandial glucose responses than beta‐glucans added to other carbohydrate containing foods. Whereas the effect of beta‐glucans in reducing post‐prandial blood glucose responses is well established, the evidence provided is insufficient to establish such an effect at doses of 1.3 g beta‐glucans per 25 g of available carbohydrate incorporated into ready‐to‐eat breakfast cereals manufactured via pressure cooking (i.e. either batch cooking or extrusion).